Poshumanisme dalam Alkitab: Sebuah Renungan Biblis di Masa Covid-19 - Robert Setio (IAKN Ambon, 2020)
Anthropocentrism has received many challenges since the publication of the famous article by Lynn White, Jr. in 1967. Yet, since then there has been no significant changes with regard to human attitude towards nature. Human beings still perceive nature as their tool whose existence is to serve their own interests. When the COVID-19 pandemic hits the world, the anthropocentrism is once again challenged. It should be a good opportunity to change the anthropocentrism. The novel corona virus has made people look powerless. It is just a tiny thing, but it has caused a great impact on human life. Despite the fact that the virus often outsmarts human beings, there is no sign that human beings want to admit their weakness. Through reading some biblical stories: the creation of human beings, the naming of animals, Job and the lamb in the Book of Revelation this article wants to deconstruct the view that sees human beings as superior to others in nature. This reading will use posthumanism as theory. It will allow us to see in the stories that human can be subjugated to animals.Â AbstrakPandangan antroposentrisme telah digugat sejak kemunculan artikel Lynn White, Jr. di tahun 1967. Tetapi sejak itu belum ada perubahan yang signifikan. Manusia masih menempatkan alam sebagai sarana untuk meraih kepentingan dirinya. Ketika pandemi COVID-19 melanda dunia, pandangan antroposentrisme kembali ditantang. Seharusnya ini menjadi kesempatan yang baik bagi manusia untuk mengubah pandangannya itu. Virus corona baru telah membuat manusia kalang kabut. Kehebatan manusia menjadi tidak berarti ketika menghadapi virus yang kecil dan tidak kelihatan itu. Tetapi bukannya menyadari akan kelemahan dirinya dan bersedia membuka diri terhadap kekuatan alam, manusia malah berupaya sedemikian rupa untuk meng-atas-i virus itu. Melalui pembacaan terhadap kisah-kisah Alkitab: penciptaan manusia, Ayub dan Wahyu, tulisan ini akan mendekonstruksi pola pikir yang mengistimewakan manusia di hadapan makhluk lainnya. Teori yang digunakan untuk menafsirkan Alkitab itu adalah poshumanisme. Poshumanisme melihat kedudukan manusia tidak lebih besar daripada makhluk-makhluk lainnya. Kebesaran binatang di hadapan manusia akan terlihat ketika kisah-kisah Alkitab itu dibaca dengan memakai teori poshumanisme.